Bioavailability of Epigallocatechin Gallate Administered with Different Nutritional Strategies in Healthy Volunteers - Vicente Andreu Fernández; Laura Almeida Toledano; Nieves Pizarro Lozano; Elisabet Navarro Tapia; María Dolores Gómez Roig; Rafael De la Torre Fornell; Óscar García Algar (MDPI AG, 2020)
The flavanol epigallocatechin gallate (EGCG) is being tested for the treatment of several diseases in humans. However, its bioavailability and pharmacokinetic profile needs a better understanding to enable its use in clinical trials. There is no consensus on the most appropriate concentration of EGCG in the body to obtain the maximum therapeutic effects. Therefore, the aim of this study is to analyze the bioavailability of EGCG orally administered alone or with different food supplements after overnight fasting in order to determine its optimal conditions (high concentrations in blood and the lowest interindividual variations) to be used as a pharmacological tool in human trials. Ten healthy volunteers (5 men and 5 women) aged 25 to 35 years were recruited prospectively. Three series of clinical experiments with a washout period of seven days among each were performed: (1) Teavigo® (EGCG extract) alone, (2) Teavigo® with a standard breakfast, and (3) FontUp® (Teavigo® commercially prepared with fats, carbohydrates, proteins, vitamins, and minerals). Blood samples were collected at 0, 30, 60, 90, 120, 180, 240, and 360 min after EGCG intake. Free EGCG in plasma was measured using a liquid chromatography and mass spectrometry UPLC-ESI-MS/MS analytical method. The pharmacokinetic variables analyzed statistically were area under the curve (AUC0-360), Cmax, Cav, Cmin, T1/2, and Tmax. EGCG (Teavigo®) alone was the group with higher AUC0-360, Cmax, and Cav both in men (3.86 ± 4.11 µg/mL/kg/6 h; 5.95 ng/mL/kg; 2.96 ng/mL/kg) and women (3.33 ± 1.08 µg/mL/kg/6 h; 6.66 ng/mL/kg; 3.66 ng/mL). Moreover, FontUp® was the group with the highest value of T1/2 both in men (192 ± 66 min) and women (133 ± 28 min). Teavigo® intake after fasting overnight revealed the highest concentration of EGCG in plasma according to its pharmacokinetic profile, indicating that this is an excellent alternative of administration if the experimental design requires good absorption in the gastrointestinal tract. Moreover, EGCG taken along with food supplements (FontUp®) improved the stability of the molecule in the body, being the best choice if the experimental design wants to reduce interindividual variation.